The Impact of Hidden Curriculum in Clinical Learning Environment: Exploring Resident’s Perceptions - Akhtar, Aisha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore and identify residents’ perceptions regarding the hidden curriculum in dermatology practice and make it explicit. Study Design: Phenomenology Qualitative study. Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital, Rawalpindi Pakistan Aug to Oct 2021. Methodology: Data was gathered from one focus group discussion and five face-to-face semi-structured interviews and analyzed by thematic analysis of the generated themes. Results: Residents described a hierarchical and competitive atmosphere in the department. Positive and negative role models were identified. Organized teaching and approachable seniors were appreciated, whereas favouritism and a lack of empathy were undervalued. Conclusion: This study highlights the hidden curriculum in dermatology and attempts to recognize its important aspects. A continuous effort should be made to unravel it and align its positive aspects with the formal curriculum. This will lead to ethical and professional doctors and better health care.